Variables Affecting the Weight and Length of Newborn Infants - Sukanto, Sukanto; Rohmawati, Indah; Muriati, Anis; Tunjung Fitriani, Evi; Suharyoto, Suharyoto (Journal of Health Sciences and Epidemiology, 2024)
Indonesia continues to face the issue of stunting. Infants with a body length of less than 48 cm and a body weight of less than 2500 grams are susceptible to stunting. This study aimed to examine the variables that impact the weight and body length of neonates. This research was characterized as observational analytic, utilizing a cross-sectional approach. The population comprises mothers who gave birth in Tulungagung Regency in 2021. The research sample consists of mothers who met the inclusion criteria for maternal pregnancies, including high-risk and got assistance from health cadres during pregnancy. The sample also includes the babies born to these mothers. The data was gathered by testing hemoglobin levels, stature, mass, mid-upper arm circumference, and the length and weight of newborn infants. The data were subjected to analysis using multiple linear regression tests. The maternal weight gain during pregnancy and mid-upper arm circumference had the potential to impact the body length and weight of the baby. Meeting the appropriate nutritional requirements during pregnancy enhances the nutritional well-being of expectant mothers, enabling them to offer optimal nourishment for their developing fetuses and promoting proper growth and development.